2019
DOI: 10.3390/s19010217
|View full text |Cite
|
Sign up to set email alerts
|

Development of a LeNet-5 Gas Identification CNN Structure for Electronic Noses

Abstract: A new LeNet-5 gas identification convolutional neural network structure for electronic noses is proposed and developed in this paper. Inspired by the tremendous achievements made by convolutional neural networks in the field of computer vision, the LeNet-5 was adopted and improved for a 12-sensor array based electronic nose system. Response data of the electronic nose to different concentrations of CO, CH4 and their mixtures were acquired by an automated gas distribution and test system. By adjusting the param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(80 citation statements)
references
References 18 publications
1
63
0
2
Order By: Relevance
“…CNNs are often benchmarked on computer vision tasks but their impacts are far wider-reaching. Recently, the studies of [1] adopted a CNN model to perform gas identification as part of the wider research area of electronic noses (ENs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CNNs are often benchmarked on computer vision tasks but their impacts are far wider-reaching. Recently, the studies of [1] adopted a CNN model to perform gas identification as part of the wider research area of electronic noses (ENs).…”
Section: Introductionmentioning
confidence: 99%
“…When finding such a trade-off, two main approaches exist. (1) The first mechanism is to scale down a large model to fit the constraints of the target device as it seems reasonable to assume that if a large increase in the size of a state-of-the-art model results in a small improvement in accuracy, then a large reduction in model size would result in a small loss of performance. While this is true to an extent, the point at which accuracy starts to drop rapidly occurs while the model is still very large.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of different active functions in CNN is discussed in Ref. [24,25]. It is found that there is a problem of gradient disappearance in saturating nonlinear functions.…”
Section: Petalmentioning
confidence: 99%
“…It is found that there is a problem of gradient disappearance in saturating nonlinear functions. The unsaturated nonlinear function can not only solve those problems, but also accelerate the convergence speed and improve the performance of CNN [25][26][27]. Therefore, the appropriate activation function in this paper is selected among Softplus, LReLU, PReLU, RReLU and ELU functions.…”
Section: Petalmentioning
confidence: 99%
“…The LeNet-5 network developed by LeCun et al [31] is a classic 2D CNN model, which has been successfully applied to Alzheimer's disease recognition [32], traffic sign recognition [33], facial expression recognition [34], gas recognition [35], pedestrian detection [36] and other fields. Due to LeNet-5 network has a relatively simple structure and a powerful classification capability, this paper employs LeNet-5 network for rolling-element bearing fault diagnosis.…”
Section: Introductionmentioning
confidence: 99%